Identyfikacja rodziców stanu chłopskiego we wrzesińskich księgach chrztu z lat 1700–1725 - Sieradzki, Andrzej (Wydawnictwo Poznańskie Studia Polonistyczne i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2011)
The study focuses on nominal groups referring to parents of peasant origin excerpted from Września-based baptismal registers (liber baptisatorum). The fundamental aim of the study is to show to what extent the folk population in the region was identified solely on the basis of a name and to what extent was the identification based on a combination of the name and the surname. It is also important to indicate whether the identification process included other elements of the noun phrase based on anthroponimic stems. Further on, it is also important to determine what type of additional and auxiliary identifying determinators are to be found with the appearing anthroponymic element. The observations done so far demonstrate that the two-element paradigm for personal identification (already common in nominal groups with reference to members of nobility and to burghers) of people that belonged to the peasantry, is used in the texts under scrutiny only to a very low degree. As the numerical data suggests, more than 80% of parents are identified by the second name only. Additional identifying elements do occur, however, in groups based on names (without the surname element). The study demonstrates that the localyzing determinator is dominant. Determinators indicating occupation, type of craft made and the current occupation of the person are also frequent. The groups under consideration also include determinators that indicate economic status of the person, though they are much rarer. The situation changes in groups with an additional surname determinator. Here, there are only two types of the determinator to be found: localizing determinator and one that indicates the economic status of a given person.
Parent identification in peasant families in Września’s baptismal records (liber baptisatorum) from the years 1700–1725
Keywords: Onomastyka; Grupa nominalna; Identyfikacja osób